Dysregulation of dopamine neurotransmission in drug addicts: implications for criminal behavior and corrective interventions - Gu, Chao; Geng, Yu-chang; Zhu, Li-na (Frontiers in Psychiatry, 2024)
Drug addiction often correlates with criminal behavior. When investigating criminal behavior among individuals grappling with drug addiction, it becomes crucial to scrutinize the influence of dopamine. Substances such as heroin, morphine, methamphetamine and other drugs can cause abnormal dopamine secretion when people are addicted to them, which promotes changes in the brain’s reward circuit and emotional balance, thereby increasing susceptibility to criminal behavior. The pivotal role of dopamine within the reward pathway and its regulatory function in emotional processes exert profound influence on behavior following drug simulation. These influences are primarily manifested by three distinct attributes: a singular criminal motive and objective, lack of moral sense, and impulsive decision-making processes. Drawing upon the distinctive dopaminergic dynamics inherent in individuals afflicted by drug addiction, this study advocates for targeted corrective interventions. The preventive paradigm encompasses the cultivation of supportive community environments, the establishment of comprehensive databases, and providing legal education and protection, among other initiatives. In terms of treatment, along with judicial sanctions and protections, exercise regimens and psychotherapeutic interventions are advocated. The corrective endeavor necessitates a synergistic integration of community-based and legalistic frameworks. The objective is to furnish guiding principles for tackling criminal behavior precipitated by aberrant dopamine secretion, underpinned by a scientifically informed approach.